The name of the game was murder - Nixon, Joan Lowery (Thorndike, Me. : Thorndike Press, 1993)
When she visits her great-uncle, a successful and self-centered author, at his fortress-like home on Catalina Island, fifteen-year-old Samantha becomes involved in his manipulative game that leads to murder.
Booklist.
Publisher's Weekly.
School Library Journal.
Young Adult
Keywords: Large type books; Authors -- Fiction; Large type books; Murder -- Fiction; Mystery and detective stories; Authors -- Fiction; Homicide -- Fiction; Mystery fiction